High prevalence of cardiovascular and respiratory abnormalities in advanced, intensively treated (transplanted) myeloma: The case for 'late effects' screening and preventive strategies. Issue 5 (27th May 2016) - Samuelson, Clare; O'Toole, Laurence; Boland, Elaine; Greenfield, Diana; Ezaydi, Yousef; Ahmedzai, Sam H.; Snowden, John A.
Abstract : Objectives : Modern management of myeloma has significantly improved survival, with increasing numbers of patients living beyond a decade. However, little is known about the long-term cardiovascular and respiratory status of intensively treated and multiply relapsed survivors. Methods : We performed detailed cardiovascular and respiratory evaluations in patients with intensively treated, advanced but stable myeloma. All patients had received at least two lines of treatment, including at least one haematopoietic stem cell transplantation procedure, but had stable, controlled disease and were off active treatment at the time of evaluation. Results : Thirty-two patients with a median duration of 6 years (range 2–12) from original diagnosis of myeloma and three lines (range 2–6) of treatment were evaluated. Despite normal physical examination in the majority, there was a high prevalence of sub-clinical cardiac and respiratory dysfunction, reflected by abnormalities of electrocardiography (45%), echocardiography (50%), serum N-terminal pro-B-type natriuretic peptide level (NT-pro-BNP, 50%), and pulmonary function testing (45%). NT-pro-BNP level correlated negatively with quality of life ( P  = 0.012) and positively with serum ferritin ( P  = 0.027). Dyspnoea score correlated with BMI ( P  = 0.001). Risk factors for cardiovascular disease (obesity, hypertension, hyperlipidaemia, and hyperinsulinaemia) were common. Discussion : Even in the absence of overt clinical features, the majority of intensively treated long-term survivors of myeloma have established cardiovascular and/or respiratory dysfunction, above levels expected in the general population of a similar age. Conclusion : This study supports routine screening and lifestyle modification combined with primary and secondary preventive strategies to reduce cardiovascular and respiratory disease and to preserve quality of life in transplanted myeloma patients.